Role of Data Centers in Healthcare Technology - Triplett, William J. (Gemilang Maju Publikasi Ilmiah (GMPI), 2025)
This article examined changes in data centers for healthcare consumers, how they improve efficiency and security, and patient-centered care. Thus, analyzing literature from 2020-2024, it outlines trends, advantages, and disadvantages of using healthcare data centers and explores possibilities of their integration with other technologies, including AI and blockchain. Research indicates that the healthcare sector could not achieve the digital front without data centers, but these centers would demand heavy capital and a robust security system for optimum results. The research points to the fact that there is still a strong need to invest and work on improving the technologies in managing health care data.